The relationship between esports and cognitive function: A scoping review - Mingyang Lu; Hwanho Lee; Inae Yoon (PLoS ONE, 2026)
The aim of this scoping review was to map and synthesize empirical evidence on the relationship between esports participation and cognitive function, with particular attention to executive control, attentional processes, visuospatial working memory, decision-making, and lifestyle-related factors. Searches were conducted in PubMed and Web of Science following PRISMA-ScR guidance. Nine empirical studies met the inclusion criteria and were included in the final synthesis. The included evidence consisted mainly of cross-sectional comparisons, together with a small number of intervention, acute experimental, and qualitative studies. The studies were organized into three thematic domains: cognitive differences across expertise levels, lifestyle and intervention effects on cognitive performance, and decision-making or training mechanisms. Five studies primarily examined expertise-level differences, three addressed lifestyle, health load, or intervention-related factors, and one focused on decision-making and training processes. Overall, the available evidence suggests that competitive esports players may show advantages in selected cognitive domains, particularly executive control, attentional flexibility, and visuospatial processing. However, findings were heterogeneous across game genres, participant classifications, cognitive tasks, and reporting practices. Because only nine studies were eligible and most designs were cross-sectional, the current evidence base remains insufficient for strong causal conclusions about whether esports participation improves cognitive function or whether pre-existing cognitive abilities contribute to esports expertise. Future research should use longitudinal, experimental, and cross-cultural designs with standardized cognitive measures and transparent reporting of statistical results.